Fatigue Life of Al-Honeycomb Core Composites Construction - Čapka, Alexander; Rusnakova, Sona; Žaludek, Milan; Karvanis, Konstantinos (Manufacturing Technology Journal, 2018)
Polymer composite honeycomb sandwich panels (PCHSPs) are used in many sectors of industry, such as in aerospace, defense and public transport factory. Sandwich panels consist of two facing skins and the core. Products of all industry sectors have to meet requirements on their dependability. This research paper deals with a proposal of the most appropriate methodology for dependability testing of PCHSPs products used in transport industry. Dependability is a global concept that includes terms such as availability, reliability, durability, maintainability, supportability, etc. The experiments have shown S-N curves with damages and without damages of PCHSPs. An important part of dependability is to be fonded the limit states of the studied object, which are for PCHSPs are characterized by fiber cracking and (core) delamination. Dependability evaluation consists of analysis and tests. For every test, it is necessary to be developed its test plan. Facing skin components of the sandwich panels may particularly be damaged. There are several methods of non-destructive testing, which can be used to determine the damage of facing skins of sandwich panels. Infrared thermography (IRNDT) is one of them. IRNDT utilizes thermo-physical properties of the materials, including thermal diffusivity.
Keywords: composite sandwich panel; honeycomb core; three-point bending; S-N curve; fatigue life